The limits of relational governance: Sales force strategies in the U.S. medical device industry - Chatterji, Aaron K.; Cunningham, Colleen M.; Joseph, John E. (Strategic Management Journal, 2019)
Research Summary : We explore how interorganizational relationships shape firm boundary decisions. Using data on 545 U.S. medical device manufacturers' product portfolios and sales‐governance choices (i.e., internal or external sales forces) from 1983 to 1996, we find relational capital between manufacturers and external sales forces influences future firm boundary decisions. Relational capital lowers the likelihood of integrating the sales function, but only when firms remain focused on the same product market. Further, launching an innovative product has a nuanced effect. For firms lacking relational capital, innovation increases the likelihood of sales integration. This pattern reverses as relational capital accumulates, but only when innovations are in the firm's existing focal product market. Our findings suggest important limits on the effect of relational governance on firm strategy. Managerial Summary : Choosing between in‐house or external sales is a key strategic decision. In the medical device industry, this decision is particularly important because salespeople are conduits between R&D and customers. For firms who initially choose external sales, the trade‐off between maintaining existing links (via external sales) and developing new, direct relationships (by bringing sales in‐house) can change significantly as product portfolios change. Analyzing 545 U.S. medical device manufacturers from 1983 to 1996, we find that existing relationships with external sales forces reduce the likelihood of bringing sales in‐house, but only when firms remain in the same product market, such as orthopedic implants. When firms launch products in new markets, especially innovations, they are more likely to bring sales in‐house.